(untitled) (Journal of Applied Learning and Teaching, 2022)
Motivation is important for students’ mathematics learning at schools. Low levels of motivation among students in mathematics in Papua New Guinea (PNG) is a concern for schools. The present status of motivation can be diagnosed through survey questionnaires. The purpose of the present study is to examine the validity and reliability of a motivation scale questionnaire using the Rasch model (Partial Credit Model). The instrument consists of 20 survey questions that were adapted from Trends in International Mathematics and Science Study (TIMSS) and Programme for International Student Assessment (PISA) studies because there are no specific items developed in the PNG context to measure motivation scale as a single factor. These questionnaires are validated using ACER ConQuest 4.0 software. The item separation index indicates good variability of the items and the items functioned well. All infit measures of the motivation scale questionnaires satisfy the Rasch model’s criteria except one item that does not conform to the requirements of Rasch measurement model.